THE REPRESENTATION OF THE TERM "PEH" IN JAVANESE LANGUAGE IN THE TULUNGAGUNG REGION - Ningsih, Ayu Setia; Rohmah, Galuh Nur (Annual International Conferences on Language, Literature, and Media; Vol 5 (2023): The 5th Annual International Conference on Linguistics, Literature, and Media (AICOLLIM)DO - 10.18860/aicollim.v5i1.2449, 2023)
A variety of meanings can be found among the different languages in Indonesia, with approximately 700 languages spoken by the country's population today. One of these languages is Javanese. The Javanese language holds multiple roles, such as a source of pride, a means of interaction and communication, and a symbol of identity. Preservation efforts are ongoing, there are still numerous Javanese vocabulary words whose meanings remain unfamiliar to some individuals. Besides regional disparities, cultural and traditional influences contribute to these differences, leading to a lack of comprehension about certain vocabulary words, like the term "PEH" in Javanese from the Tulungagung region. A profound comprehension of the conveyed meaning or intention makes it easier and assists in interpreting the intended word. This helps resolve issues and imparts lessons for both the speaker and the listener during communication. Additionally, it streamlines the process of acquiring correct and precise information. In every region where Javanese is spoken as a native language, differences exist not only in terms of vocabulary, but also in speaking mannerisms. Misunderstandings and numerous inquiries provide the foundation for addressing curiosity and messages. There are numerous conjectures concerning expressions in Javanese, like "PEH" in the Tulungagung region. This methodology employs a qualitative approach using interview techniques. This approach is employed to understand the representation of the term "PEH" in Javanese language in the Tulungagung region. The representation of the term "PEH" in Javanese language in the Tulungagung region holds various meanings contingent upon the context and temporal application. The utilization of "PEH" carries individualized representations, while preserving commonalities across several interpretations.